Survival outcomes of diffuse large B-cell lymphoma by association with concurrent or antecedent follicular lymphoma and double hit status. Issue 13 (10th November 2019) - Behdad, Amir; Boddy, Craig S.; Fought, Angela J.; Taxter, Timothy; Falkiewicz, Marissa K.; Ayers, Emily; Chen, Qing C.; Chen, Yi-Hua; Karmali, Reem; Pro, Barbara; Winter, Jane N.; Landsburg, Daniel J.; et al.
Abstract: Diffuse large B-cell lymphoma (DLBCL) transformed from follicular lymphoma (FL) (tDLBCL) has been traditionally associated with an aggressive course, but more recent studies have shown longer survivals. The clinical significance of concurrent FL at the time of diagnosis of DLBCL (cDLBCL/FL) is less clear. We compared outcomes of tDLBCL, cDLBCL/FL, and de novo DLBCL (dDLBCL) and then evaluated the impact of double hit (DH) rearrangements (MYC with BCL2 and/or BCL6) in these subgroups' outcomes. The progression free survival (PFS) and overall survival (OS) were not significantly different among the three groups (dDLBCL, tDLBCL, and cDLBCL/FL). The effect of DH on survival was then analyzed in two subgroups: (1) dDLBCL and (2) tDLBCL + cDLBCL/FL. PFS and OS were significantly shorter in lymphomas with DH in each of these two subgroups. We conclude that DH status drives outcomes in all DLBCLs, regardless of their transformation status.